Fixes and Flux: Frontier Brokers, Political Settlements and Post-War Politics in Nepal and Sri Lanka. Issue 11 (2nd November 2022) - Goodhand, Jonathan; Walton, Oliver
Abstract: This article examines post-war politics in Nepal and Sri Lanka through the prism of centre-periphery relations, drawing upon and expanding political settlements analysis. We highlight two key features neglected in existing research on political settlements: first, the spatial dimensions of these settlements – particularly the salience of frontier regions in shaping post-war orders. These 'sensitive spaces' continue as sites of struggle in the post-war period and frontier battles over the reordering of space and the delineation of rights, authority and citizenship are central to the emergence of post-war political settlements. Second, within these post-war frontiers we highlight the role of 'frontier brokers' who mediate between national and local levels of the political system. Post-war frontiers provide an opening and a demand for brokers who act as both gatekeepers and go-betweens, balancing demands from communities at the margins with the need to forge alliances and extract resources from central actors. We argue that questions of space and agency need to be foregrounded in political settlement analysis, and studying the lives of frontier brokers provides a lens for understanding shifts in political settlements and the changing relationship between the national and subnational levels of the political system at war's end.